A NOVEL ACYCLIC DITERPENIC ALCOHOL ISOLATED FROM ANTIOXIDANT ACTIVE ETHANOL EXTRACT OF LEAVES OF CENTAUROTHAMNUS MAXIMUS GROWN IN SAUDI ARABIA - SIDDIQUI, NASIR ALI; Al Enezi, Mohammed A.; Alam, Perwez; Haqque, Anzarul; Ali, Mohammad (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Isolation and characterization of a new compound from the antioxidant active ethanol extract of leaves of an endemic plant Centaurothamnus maximus. Methods: The air dried powdered leaves of the plant was extracted successively with n-hexane, dichloromethane, ethyl acetate and ethanol. The obtained extracts were concentrated under reduced pressure using rotary evaporator. The antioxidant activity was carried out on various concentrations (1000, 500, 100, 50 and 10 µg/ml) of all the extracts by DPPH free radical scavenging method. After screening for antioxidant potential the ethanol fraction was selected for the isolation of phytoconstituents by column chromatography using LiChroprep RP-18 as stationary phase and water, MeOH and CHCl3 in different combinations as eluent. The chemical structures of the isolated compounds were elucidated by 1D and 2D NMR spectroscopic techniques (DEPT, COSY, H M B C and HSQC) aided by EIMS mass and IR spectra. Results: The antioxidant activity of ethanol extract was highly comparable with standard ascorbic acid as compared to other extracts. A new compound along with two known compounds has been isolated from antioxidant active ethanol extract. The chemical structure of unknown compound was established as 2, 6, 10, 14-tetramethyl hexadec-12-cis-en-5α, 7α, 9α, 14α-tetraol (CM1) while the known compound isolated Luteolin-7-O-β-glucopyranosyl-6’’-O-(6’’→1’’’)-β-D-rhamno-pyranoside (CM-2) and stigmast-5,22–dien-3β –ol (CM3). Conclusion: On the basis of interpretation of different spectroscopy data we concluded that the compound CM1 is an acyclic diterpenic alcohol. The authors are reporting the isolation of CM1 from plant source for the first time but CM2 and CM3 are known compounds. Ethanol extract of leaves can be recommended as potent antioxidant for ethno-medical purposes. The antioxidant properties might be due to some well-known antioxidants like (CM-2) and other falvonoidal compounds.